Investigating subtle kidney injury in primary hyperparathyroidism by means of sensitive and specific biomarkers. (1st August 2019) - Cipriani, Cristiana; Pepe, Jessica; Colangelo, Luciano; Fassino, Valeria; Occhiuto, Marco; Biondi, Piergianni; Nieddu, Luciano; Minisola, Salvatore
Abstract: Objective: Kidney involvement is a common complication in primary hyperparathyroidism (PHPT). No study so far has assessed the prevalence of kidney injury developing before the reduction in glomerular filtration rate (GFR) in PHPT. The study was aimed at establishing the potential role of biomarkers of kidney injury in detecting subtle renal damage in patients with PHPT. Design: Cross‐sectional study. Patients: A total of 69 postmenopausal patients with PHPT and 41 healthy age‐ and sex‐matched subjects were studied. Exclusion criteria were as follows: GFR < 30 mL/min, chronic inflammatory disease, nephrotic syndrome, infection, malignancy, heart failure, recent exposure to iodinated contrast media or nonsteroidal anti‐inflammatory drugs. Measurements: We measured a panel of sensitive biomarkers of kidney injury in PHPT vs controls. Results: Mean FGF23 and Klotho were higher in PHPT (72 ± 48 and 811 ± 366 pg/mL, respectively) than controls (53 ± 23.5 and 668.6 ± 17; P < .02 and P < .05). Urine KIM‐1/uCr was significantly higher in PHPT (1.4 −6 ± 1.3 −6 ) than controls (9.2 −7 ± 7 −7 ; P < .05); this was particularly evident in the CrCl 60‐89 mL/min category (1.3 6 ± 9 7 vs 8.2 −7 ± 3.6 −7 ; P < .02). Mean values of urine NGAL/uCr were higher in PHPT with (n = 28) compared to those without kidney stones (n = 35; 1.8 −5 ± 1.4 −5 and 1 −5 ± 8 −6 ; P < .0001). We found significant positive associations between urine NGAL/uCr and Ca ( R = .292, P < .02) and urine KIM1/uCr and PTH ( R = .329, P < .01). Conclusions: We propose the utilization of these molecules, particularly urine KIM‐1/uCr and urine NGAL/uCr ratios for the assessment of subtle kidney injury in patients with PHPT. These molecules are elevated in tubular necrosis and have potential role in the development of kidney damage in PHPT, according to the severity of the disease.